The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1590/s1517-83822011000400008
|View full text |Cite
|
Sign up to set email alerts
|

A 7-year survey of superficial and cutaneous mycoses in a public hospital in Natal, Northeast Brazil

Abstract: In the present study, we determined the frequency of superficial and cutaneous mycoses and their etiologic agents during a 7-year period (2002–2008) in Natal, Brazil. A total of 1,717 specimens of skin, nail, and hair were collected from 1,382 patients with suspected mycoses lesions and were then subjected to direct microscopy and culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 19 publications
4
10
1
Order By: Relevance
“…Indeed, onychomycoses are thought to account for approximately 33% of all fungal skin infections and 50% of all nail disorders. 28 Similar to our findings, some studies also have reported onychomycosis as the most prevalent type of dermatomycoses in various geographical areas, such as Brazil, 23,26 Chile, 25 Mexico, 24 Turkey 3,6,27 and Saudi Arabia. 4 Lopez-Martinez et al 24 hypothesized that the rising incidence of onychomycosis observed in the last decades could be the result of patients seeking treatment more frequently for ungual dystrophies, leading to an increase in the diagnosis of onychomycosis.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Indeed, onychomycoses are thought to account for approximately 33% of all fungal skin infections and 50% of all nail disorders. 28 Similar to our findings, some studies also have reported onychomycosis as the most prevalent type of dermatomycoses in various geographical areas, such as Brazil, 23,26 Chile, 25 Mexico, 24 Turkey 3,6,27 and Saudi Arabia. 4 Lopez-Martinez et al 24 hypothesized that the rising incidence of onychomycosis observed in the last decades could be the result of patients seeking treatment more frequently for ungual dystrophies, leading to an increase in the diagnosis of onychomycosis.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown that both the prevalence and aetiology of dermatomycoses can change according to different countries and can even vary within a country. 3,4,6,[23][24][25][26][27] In our study, onychomycosis was the most common clinical condition, and toenail infections were particularly common, representing 76.3% (71/93) of the cases of onychomycosis and 32.9% (71/216) of all cases. Indeed, onychomycoses are thought to account for approximately 33% of all fungal skin infections and 50% of all nail disorders.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, microscopy remains a sensitive easily implemented method for the diagnosis of PV. The rate of positive cases detected mycologically among the total number of patients received in the department during the study period (10.8%) is higher than those reported in several studies from Brazil on the epidemiology of dermatomycosis in hospital settings, which reported rates of 4.5% (Sylva-Rocha et al, 2016), 9.5% (Calado et al, 2011) and 2.1% (Di Chiacchio et al, 2014). In contrast, a higher prevalence (37.31%) was reported in Burkina Faso (Zida et al, 2015) among prisoners of Ouagadougou.…”
Section: Discussioncontrasting
confidence: 53%
“…The incidence of cutaneous mycoses is growing in an alarming proportion all over the world [1,2]. The contribution of various lifestyle changes and associated disorders in the incidence and prevalence of cutaneous mycoses is quite significant.…”
Section: Introductionmentioning
confidence: 99%